Construction of a Large Composite Gridshell Structure: A Lightweight Structure Made with Pultruded Glass Fibre Reinforced Polymer Tubes. Issue 2 (1st May 2016) - du Peloux, Lionel; Tayeb, Frédéric; Baverel, Olivier; Caron, Jean-François
Abstract: The Ephemeral Cathedral of Créteil at Paris, France, is a gridshell structure made of composite materials. Built in 2013, this 350 m 2 religious edifice is a temporary church meant to gather the parishioners during the two year renovation of their permanent cathedral. This large-scale prototype represents a first in the building industry which still shows excessive apprehension for the use of non-traditional materials such as composites, especially when it comes to structural applications.